LED fluorescence microscopy in the diagnosis of tuberculosis: Fading and restaining of smears for external quality assessment - Allassia, Sonia (2016)
Fil: Allassia, Sonia. Dirección de Bioquímica de la Municipalidad de Rosario, Rosario, Santa Fe; Argentina.